Semiotic Analysis: Social Critics Towards Government Depicted in The Songs of Marjinal Band - Sihombing, Lambok Hermanto (Universitas Negeri Surabaya, 2021)
This research aimed to determine the meaning of the songs belonged to Marjinal band, a punk band whose songs contain critics to the government. The songs that the reasearchers analyzed were Hukum Rimba and Buruh Tani. The researchers used the data taken from various digital platforms and analyzed the lyrics using Semiotic Theory from Ferdinand De Saussure. Furthermore, the results of the research from Hukum Rimba and Buruh Tani song implied that people who had money and power would be spared by the law. Meanwhile, the poor would always be oppressed by the law.Keywords: critics, government, lyrics, money, power